Isolation of exosome-like nanovesicles from Yiqi Huoxue Jiedu decoction and their anti-ovarian cancer activity - Song, Qing-Ya; Cui, Yong-Jia; Lu, Wen-Ping (Frontiers in Pharmacology, 2025)
BackgroundOvarian cancer, the deadliest gynecologic malignancy, is marked by high recurrence and poor prognosis. Exosome-like nanovesicles (ELNVs) derived from decocted traditional Chinese medicine (TCM) formulas encapsulate key bioactive components, and show promising therapeutic efficacy with good biocompatibility and targeting ability. However, research on ELNV extraction methodologies remains limited. Yiqi Huoxue Jiedu Decoction (YQHXJDD), an empirically validated TCM formula for ovarian cancer, lacks systematic investigation into its ELNV isolation protocols and therapeutic mechanisms. This study took YQHXJDD as the research subject, with a focus on extracting ELNVs from this TCM formula and validating their anti-ovarian cancer activity.MethodsYQHXJDD was extracted using varied decoction protocols. ELNVs were enriched by gradient and ultracentrifugation, resuspended in phosphate-buffered saline, and were characterized by size and concentration using transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA). The number of ELNVs enriched per dose of YQHXJDD was calculated to screen the decoction method that maximized ELNV yield and aligned with clinical medication practices. The colloidal stability of YQHXJDD ELNVs was evaluated via zeta potential measurement, and the bioactive components of YQHXJDD ELNVs were identified using untargeted metabolomics and RNA sequencing. An ID8-Luc peritoneal tumor-bearing mouse model was established and randomized into three groups: model, YQHXJDD, and YQHXJDD ELNVs. Mice received oral gavage for 3 consecutive weeks. Tumor burden was monitored via in vivo small animal imaging. Immunofluorescence was used to quantify CD86, CD206, CD4, and CD8 fluorescence in omental tumors. Luminex xMAP® Multiplex Assay was used to detect 36 cytokines/chemokines in serum, and flow cytometry was used to analyze splenic immune cell proportions and activity.ResultsThe creation efficiency of ELNVs formed during decoction is the highest with the optimal protocol, which is identified for maximizing YQHXJDD ELNV yield and involves 40 min of high-heat treatment followed by an additional 30 min of low-heat treatment. Zetaview-based zeta potential analysis demonstrated that YQHXJDD ELNVs by this protocol had an average zeta potential of −35.52 mV, indicating favorable colloidal stability. Untargeted metabolomics analysis revealed “Lipids and lipid-like molecules” as the most abundant metabolite superclass (34.98% of total metabolites), while “Carboxylic acids and derivatives” represented the dominant subclass (11.66%). Regarding small RNAs, those enriched in YQHXJDD ELNVs were confirmed to be typical, functionally active small RNAs. Notably, miR8783 and other miRNAs exhibited significantly high expression, along with high conservation and abundance across samples, suggesting they might act as core regulators of YQHXJDD ELNV biological functions. In in vivo assessments, compared with the model group, YQHXJDD ELNVs significantly inhibited ovarian cancer growth and metastasis, increased tumor necrosis factor-α (TNF-α) levels in mouse peripheral blood, and positively regulated the M1/M2 macrophage ratio and CD4+/CD8+ T cell ratio in omental tissues (all P < 0.05). However, YQHXJDD ELNVs had no significant effect on the proportions of splenic effector T cells, natural killer (NK) cells, activated CD8+ T cells, and activated NK cells (all P ≥ 0.05).ConclusionThe decoction ELNVs isolated from YQHXJDD can inhibit the growth and dissemination of ovarian cancer. The miRNAs and lipid components encapsulated in these ELNVs are presumed to be the critical mediators of these anti-ovarian cancer effects.